Association of Plasma Neurofilament Light Chain With Glycaemic Control and Insulin Resistance in Middle-Aged Adults - Thota, Rohith N.; Chatterjee, Pratishtha; Pedrini, Steve; Hone, Eugene; Ferguson, Jessica J. A.; Garg, Manohar L.; Martins, Ralph N. (Frontiers in Endocrinology, 2022)
Aims: This study aimed to determine the association of plasma neurofilament light (NfL), a marker of neurodegeneration, with diabetes status and glycaemic parameters in people with normal glycaemia (NG), pre-diabetes (PD) and type 2 diabetes (T2D). Methods: Clinical and descriptive data for the diagnostic groups, NG (n=30), PD (n=48) and T2D (n=29) aged between 40 and 75 years) were included in this cross-sectional analysis. Plasma NfL levels were analyzed by ultra-sensitive single-molecule array (Simoa) assay. Results: A positive correlation was evident between plasma NfL and fasting glucose (r = 0.2824; p = 0.0032). Plasma NfL levels were not correlated with fasting insulin and insulin resistance. Plasma Nfl levels were significantly different across the diabetes groups (T2D >PD >NG, p=0.0046). Post-hoc analysis indicated significantly higher plasma Nfl levels in the T2D [12.4 (5.21) pg/mL] group than in the PD [10.2 (4.13) pg/mL] and NG [8.37 (5.65) pg/mL] groups. The relationship between diabetes status remained significant after adjusting for age, sex, BMI, HOMA-IR and physical activity (adjusted r2 = 0.271, p = 0.035). Participants in the top Nfl tertile (>12.2 pg/mL) were relatively older with higher fasting glucose levels than the other two tertiles. Conclusions: These results show biomarker evidence of neurodegeneration in adults at risk or with T2D. Larger sample size and longitudinal analysis are required to better understand the application of NfL in people with risk and overt T2D.